2023
DOI: 10.1002/hbm.26202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating test–retest reliability and sex‐/age‐related effects on temporal clustering coefficient of dynamic functional brain networks

Abstract: The multilayer dynamic network model has been proposed as an effective method to understand the brain function. In particular, derived from the definition of clustering coefficient in static networks, the temporal clustering coefficient provides a direct measure of the topological stability of dynamic brain networks and shows potential in predicting altered brain functions. However, test–retest reliability and demographic‐related effects on this measure remain to be evaluated. Using a data set from the Human C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 112 publications
0
26
0
Order By: Relevance
“…For dFC studies, there have been also several studies to investigate the possible sex effects on the temporal stability of brain networks. Interestingly, although conflicting results exist [46], we notice many of these studies found that the females' brain networks seem to be more stable over time compared to the males' brain networks [14,43,47]. For instance, one research using a state-clustering algorithm suggested that the females' brain networks switch connectivity states less frequently than the males' and can thus be considered more stable over time [43]; in another study using the temporal clustering coefficient, it was found that the females' brain networks are more stable than the males' and such differences are significant at both the global and regional (particularly within the default-mode and subcortical regions) levels [14].…”
Section: Possible Influencing Factors When Analyzing the Temporal Sta...mentioning
confidence: 88%
See 4 more Smart Citations
“…For dFC studies, there have been also several studies to investigate the possible sex effects on the temporal stability of brain networks. Interestingly, although conflicting results exist [46], we notice many of these studies found that the females' brain networks seem to be more stable over time compared to the males' brain networks [14,43,47]. For instance, one research using a state-clustering algorithm suggested that the females' brain networks switch connectivity states less frequently than the males' and can thus be considered more stable over time [43]; in another study using the temporal clustering coefficient, it was found that the females' brain networks are more stable than the males' and such differences are significant at both the global and regional (particularly within the default-mode and subcortical regions) levels [14].…”
Section: Possible Influencing Factors When Analyzing the Temporal Sta...mentioning
confidence: 88%
“…Interestingly, although conflicting results exist [46], we notice many of these studies found that the females' brain networks seem to be more stable over time compared to the males' brain networks [14,43,47]. For instance, one research using a state-clustering algorithm suggested that the females' brain networks switch connectivity states less frequently than the males' and can thus be considered more stable over time [43]; in another study using the temporal clustering coefficient, it was found that the females' brain networks are more stable than the males' and such differences are significant at both the global and regional (particularly within the default-mode and subcortical regions) levels [14]. These findings may not only highlight the necessity to control for sex effects in dFC studies, but also provide valuable insight into the sex differences in clinical characteristics of many mental problems and diseases (e.g., females are more likely to be affected by depression) [48][49][50].…”
Section: Possible Influencing Factors When Analyzing the Temporal Sta...mentioning
confidence: 88%
See 3 more Smart Citations